Strand‐specific, high‐resolution mapping of modified RNA polymerase II - Laura Milligan; Vân A Huynh‐Thu; Clémentine Delan‐Forino; Alex Tuck; Elisabeth Petfalski; Rodrigo Lombraña; Guido Sanguinetti; Grzegorz Kudla; David Tollervey (Molecular Systems Biology)
Abstract Reversible modification of the RNAPII C‐terminal domain links transcription with RNA processing and surveillance activities. To better understand this, we mapped the location of RNAPII carrying the five types of CTD phosphorylation on the RNA transcript, providing strand‐specific, nucleotide‐resolution information, and we used a machine learning‐based approach to define RNAPII states. This revealed enrichment of Ser5P, and depletion of Tyr1P, Ser2P, Thr4P, and Ser7P in the transcription start site (TSS) proximal ~150 nt of most genes, with depletion of all modifications close to the poly(A) site. The TSS region also showed elevated RNAPII relative to regions further 3′, with high recruitment of RNA surveillance and termination factors, and correlated with the previously mapped 3′ ends of short, unstable ncRNA transcripts. A hidden Markov model identified distinct modification states associated with initiating, early elongating and later elongating RNAPII. The initiation state was enriched near the TSS of protein‐coding genes and persisted throughout exon 1 of intron‐containing genes. Notably, unstable ncRNAs apparently failed to transition into the elongation states seen on protein‐coding genes.